Utilization of alternating current methods for manufacture of selective absorbing coatings for heat collectors - Klochko, N.P.; Volkova, N.D.; Starikov, V.V.; Kopach, V.R.; Dobrotvorskaya, M.V.; Mateychenko, P.V.; Novikov, V.O. (Functional Materials, 2005)
Electrochemical processes, taking place during alternating current treatment of aluminum, and dependence of morphology, chemical composition and electrical properties of obtained surface on treatment regimes have been studied. The conditions, providing the formation of selectively absorbing Al/Al203 coating in hydrochloric acid solutions, have been determined. To improve the optical characteristics of such coatings we have elaborated an electrochemical alternating current deposition of cupric oxide on their surface in form of isolated CuО nanoparticles. The method is environmentally safe and does not require any re-equipment. It provides an enhanced spectral selectivity due to increase of sunlight absorption in visible spectral region without a significant emissivity increase in the infrared one.